Ethnomedicinal knowledge of Temiar ethnic tribe of Lojing Highlands, Kelantan: a source for nutritional and antioxidant potential - Pasupuleti Visweswara Rao; Lee, Lih Huey; Shamsul Mohamed; Ikarastika Rahayu Abdul Wahab; Soon, Jan Mei (Basha Research Corporation, 2016)
Traditional medicinal plants have been consumed and practised by the Orang Asli of Peninsular Malaysia for centuries. Temiar is one of the sub-ethnics under the Orang Asli (Senoi) tribe. The Temiar ethic tribe utilises indigenous plants for treatment of illnesses and general healthcare. Since the indigenous people transmit knowledge orally; their knowledge is comparatively more vulnerable to extinction. Besides, deforestation and conversion of forest land into farms also contributed to loss of habitat of traditional medicine and food plants. Hence. the objectives of this study are to establish a proﬁle of ethnomedicinal knowledge of indigneous plants utilised by the Temiar tribe in Loiing Highlands. Field study was carried out to document the various plants used to treat diseases and their methods of preparation. Antioxidant activity has been carried out by free radical scavenging (DPPH) assay with 95% ethanolic extracts of Ageratum conyzoides (A. conyzoides) and Phyllanthus niru/‘I (P. niruri). The inhibition concentrations at lC50 for both plant extracts were found to be 29.79 mg/mL and 34.37 mg/mL, respectively. The results were compared to the butylated hydroxytoluence (BHT). The present study successfully documented the indigenous knowledge of medicinal plants usage and identiﬁed potentially high value medicinal plants species that can be used for the economic development of thenation. Additionally. the identiﬁcation of potentially nutritional medicinal plants and vegetables will contribute to a more diversiﬁed diet and food security of the Temiar tribe.